The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s12032-010-9811-x
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant chemoradiotherapy using low-dose weekly gemcitabine versus low-dose weekly paclitaxel in locally advanced head and neck squamous cell carcinoma: a phase III study

Abstract: The objective of this study was to compare concomitant chemoradiotherapy based on weekly low-dose gemcitabine versus weekly low-dose paclitaxel in locally advanced head and neck squamous cell carcinoma. Previously, untreated patients with locally advanced squamous cell carcinoma of the head and neck were randomly assigned to one of the two concomitant chemoradiation regimens: (1) weekly gemcitabine at a dose of 100 mg/m(2) over 30 min 1-2 h before radiotherapy and (2) weekly paclitaxal at a dose of 20 mg/m(2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…Several randomized trials have since been updated and new trials reported in the indexed medical literature that were not considered in the present analysis. Some of these have used newer and more potent chemotherapeutic agents or targeted therapy concurrently with RT that may further enhance the efficacy of the concomitant regimen. In parallel, some recent reports of altered fractionation RT have also demonstrated much larger survival benefit than was demonstrated by the MARCH meta‐analysis and are being included in an updated meta‐analysis of altered fractionation (MARCH 2).…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized trials have since been updated and new trials reported in the indexed medical literature that were not considered in the present analysis. Some of these have used newer and more potent chemotherapeutic agents or targeted therapy concurrently with RT that may further enhance the efficacy of the concomitant regimen. In parallel, some recent reports of altered fractionation RT have also demonstrated much larger survival benefit than was demonstrated by the MARCH meta‐analysis and are being included in an updated meta‐analysis of altered fractionation (MARCH 2).…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel -representative of the second generation chemotherapy -has been used in SCCHN single-agent [7,14] or platinum-based radiochemotherapy protocols [2,6,8,15,22,25]. Current treatment strategies often use hyperfractionated or hyperfractionated-accelerated radiotherapy protocols to enhance efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin, the most common agent, may lead to significant side effects and cannot be used in many patients with recurrent SCCHN (7). Beside other systemic treatments, paclitaxel may be an alternative option for these patients, which has been reported to be effective and associated with favorable toxicity profiles (8)(9)(10). For example, in a prospective study of 35 patients with locally advanced SCCHN, 70.2-72 Gy of radiotherapy plus three courses of paclitaxel resulted in a median survival of 56.5 months, and most toxicities were grade 2 or less (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, many patients, particularly in recurrent disease after chemoradiation, may not be able to receive platin-based chemotherapy again due to expected toxicity such as nausea, vomiting and renal failure (7). For these patients, taxanes may be an alternative option, since these agents have been proved effective as a monotherapy in patients with SCCHN (8)(9)(10). In addition to concurrent chemotherapy, twice-daily administration of radiotherapy with lower doses per fraction (e.g.…”
mentioning
confidence: 99%